The transcript cleavage factor paralogue TFS4 is a potent RNA polymerase inhibitor - Thomas Fouqueau (Nature Portfolio, 2017)
Transcript cleavage factors such as eukaryotic TFIIS assist the resumption of transcription following RNA pol II backtracking. Here the authors find that one of the Sulfolobus solfataricus TFIIS homolog—TFS4—has evolved into a potent RNA polymerase inhibitor potentially involved in antiviral defense.